Sikap Keberagamaan Masyarakat Menghadapi Wabah COVID-19 - Dadang Darmawan; Deni Miharja; Roro Sri Rejeki Waluyajati; Erni Isnaeniah (UIN Sunan Gunung Djati Bandung, 2020)
The purpose of this study is to describe the religious attitudes of the Muslim amid COVID-19 outbreak. Many muslims are very depressed, because the government and related authorities are trying to ban worship activities in mosques during COVID-19 pandemic. Many Muslims find it hard to leave their custom of worship together at the mosque. Many of them are still praying together in the mosque. This phenomenon is the object of the study. The results show that the pattern of worship activities carried out by Muslims amid COVID-19 pandemic has changed. At the surface level, it appears that mosques tend to be empty and closed. At a deeper level, we see a unique pattern that involves four variables: the obligation of worship, the worship participation, the encouragement of social distancing, and the rationality of Muslims.